2020
DOI: 10.1111/obr.13163
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing obesogenic behaviours of adolescent girls and women in low‐ and middle‐income countries: A qualitative evidence synthesis

Abstract: Summary This systematic review synthesized the qualitative evidence on factors influencing obesogenic behaviours in adolescent girls and women of reproductive age in low‐ and middle‐income countries (LMICs). This qualitative evidence synthesis followed the framework synthesis approach to extract, analyse and synthesize data. Electronic searches were conducted in the Web of Science, SCOPUS, CABI Abstracts, MEDLINE, PsycINFO and Google Scholar. Studies were eligible if they were conducted in LMICs, of qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 127 publications
(762 reference statements)
3
52
0
Order By: Relevance
“…This qualitative study provides a useful perspective on the relationship between food retail and dietary preferences across various levels of influence in Kisumu and Homabay Counties in Western Kenya. Consistent with other findings [ 23 , 24 ]. The results of this study demonstrate that the influences on dietary preference and local foodscapes are multifaceted.…”
Section: Discussionsupporting
confidence: 93%
“…This qualitative study provides a useful perspective on the relationship between food retail and dietary preferences across various levels of influence in Kisumu and Homabay Counties in Western Kenya. Consistent with other findings [ 23 , 24 ]. The results of this study demonstrate that the influences on dietary preference and local foodscapes are multifaceted.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown the different roles that parents play in food consumption. Mothers preparing food at home have been described as a positive influence, whereas high-income parents who are too busy to prepare food may become negative role models (33)(34)(35). In our sample, adolescents from households with more assets also perceived that both healthy and unhealthy foods were available in their households.…”
Section: Discussionmentioning
confidence: 86%
“…The differences between private and government-school adolescents in terms of their dietary diversity and purchasing of SSBs could be explained by the socio-economic status of their families, which we assessed using the number of assets or the amount of pocket money the adolescents receive. Parents who give pocket money without spending stipulations could create financial autonomy, but the lack of supervision could also potentially worsen the unhealthy dietary behaviors of adolescents (33). Studies have shown the different roles that parents play in food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Food is unsafe when it is exposed to any hazard that makes it harmful to health, including bacterial, viral, parasitic and/or chemical toxins (FAO/WHO, 2003). Evidence suggests that financial gain or convenience of food preparation outweigh the risk associated with consuming a product (Grace et al, 2010), while fear of poor food hygiene could outweigh concerns about the nutritional quality of food (Nago et al, 2012;Trubswasswer et al, 2020). The latter finding is worrisome as food safety and nutrition are potentially closely linked and concerns limiting the consumption of fresh FFV could make packaged (often ultra-processed) food, the perceived safer option (Grace and McDermott, 2015;Trubswasser et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The latter finding is worrisome as food safety and nutrition are potentially closely linked and concerns limiting the consumption of fresh FFV could make packaged (often ultra-processed) food, the perceived safer option (Grace and McDermott, 2015;Trubswasser et al, 2020). While homecooked food is considered the safer and healthier option in LMIC settings (Rao et al, 2007;Trubswasswer et al, 2020), eating out of home continues to increase especially in the urban context (Reardon et al, 2021). Street food has become increasingly popular as it is perceived as accessible, affordable, and convenient, but can carry great risk if food safety management is not in place (Abrahale et al, 2019;Asiegbu et al, 2016;Gupta et al, 2018;Hoffmann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%